ERROR ANALYSIS OF SUBJECT-VERB AGREEMENT ON STUDENTS’ ESSAY WRITING - Jonris Tampubolon (The Seall Journal, 2020)
The purposes of this study are: 1. To find out types of error that students make in writing English essay, and 2. To analyze how students make theerrors. The study was limited on analyzing the errors on essay writing as one of question forms on students‟ monthly exam in terms of grammar errorsdealing with the subject-verb agreement and tenses. One way to address morphological, syntactic, and lexical difficulties to learners is through erroranalysis, which consists of three stages: 1) identification of errors, 2) classification of errors, and 3) identification of the causes of errors (Ferch,Haastrup, & Phillipson, 1984:22). The data of this study were collected through observation in form of documentation. The data were analyzed byidentifying the errors that students made in their writing in terms of subject verb agreement and tenses, then classifying the sources of errors based onKrashen‟ theory which classifies them into addition, ordering, mis information and deletion. The results of this study showed that thestudents still often make errors on their writing. It can be seen also in the result that the errors in terms of tense is more dominant found in thestudents‟ essay writing than the errors in terms of subject-verb agreement. There are 53.2 % percent of errors in terms of tense and the rest 46.8 % areerrors in terms of subject-verb agreement. The findings of this study showed that the number of errors made by the students on their writing is in line withthe results of the previous studies. The 186 errors in both terms subject-verb agreement and tense out of 473 total clauses has proven those studies.